Girl on pointe : Chloe's guide to taking on the world - Lukasiak, Chloe, 2001-; Ohlin, Nancy (Bloomsbury, 2018)
Summary: Lukasiak knows that life would be easier without disappointments, bullying, and medical issues... but sometimes it takes challenges to inspire you to achieve big things. From the hit reality television show Dance Moms, she has found that self-acceptance and kindness are the key to getting over the rough spots in life and realizing your passions. Now she shares that message while inspiring readers to be their very best selves. Chloe Lukasiak believes that things happen for a reason. She knows that life would be easier without disappointments, bullying, and medical issues, but sometimes it takes challenges to inspire you to achieve big things.